2020
DOI: 10.1186/s12913-020-05675-8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the effect of serious illness medical insurance on relieving the economic burden of rural residents in China: a case study in Jinzhai County

Abstract: Background: In 2003, China established a New Rural Cooperative Medical System (NRCMS) for rural residents to alleviate the burden of medical expenses among rural residents. However, its reimbursement for high medical costs was insufficient. Therefore, China gradually established the Serious Illness Insurance System (SIMIS) based on NRCM S. After receiving payment through NRCMS, patients in rural areas who met the requirements of SIMIS policy would receive a second payment for their high medical expenses. This … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Critical illness insurance was first implemented in 2012 [ 12 ]. As the Central Government provided only guidelines and a general framework for its implementation, the schemes are implemented differently in different regions [ 12 , 13 ]. In many regions, patients are eligible to receive additional reimbursement under the critical illness insurance scheme if their out-of-pocket expenses are more than the annual average disposable income per capita in the local area [ 12 , 13 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Critical illness insurance was first implemented in 2012 [ 12 ]. As the Central Government provided only guidelines and a general framework for its implementation, the schemes are implemented differently in different regions [ 12 , 13 ]. In many regions, patients are eligible to receive additional reimbursement under the critical illness insurance scheme if their out-of-pocket expenses are more than the annual average disposable income per capita in the local area [ 12 , 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…NRDL drugs are reimbursed at different rates according to whether they are included in Category A (essential and affordable drugs) or Category B (innovative and relatively more expensive drugs) [ 11 ]. For patients who meet a particular reimbursement threshold (which in many provinces is set at the local average per capita annual disposable income), additional reimbursement may be available via Critical Illness Insurance schemes, funded within the BMI schemes [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, supplemental medical insurance required a series of strict vetting processes and high admission criteria, and there were certain barriers for vulnerable people with catastrophic diseases to enter their coverage. Some studies have shown that major medical insurance has reduced the financial burden of patients with catastrophic diseases to some extent, and its coverage has been expanded compared to that of the basic medical insurance, but the coverage was still relatively small ( 20 ). Expanding medical insurance coverage coincided with Hallman’s proposed measures to address CHE and medical coverage for catastrophic diseases ( 45 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…CMI is more protective for low-income individuals, which may also be explained by their preference for health facilities when ill. Wagstaff et al discovered that the poor are more likely to seek treatment at low-level health facilities, putting less strain on their OOP expenditures [ 60 ]. Although, some research indicated that high OOP costs limit the ability of people in impoverished economic situations to benefit from the CMI and erode the CMI’s fairness [ 28 ]. CMI considers the needs of low-income residents during the gradual implementation process.…”
Section: Discussionmentioning
confidence: 99%
“…A study of rural residents discovered that CMI was insufficient in relieving rural residents’ medical burdens [ 27 ]. Due to the high out-of-pocket costs, individuals with better economic circumstances could receive CMI compensation, resulting in unfair benefits for CMI [ 28 ]. CMI increased patients’ inpatient and outpatient medical expenses, but also their out-of-pocket expenses [ 29 ].…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%